Management of epistaxis in patients with ventricular assist device: a retrospective review - Clifford Scott Brown; Ralph Abi-Hachem; David Woojin Jang (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients with a ventricular assist device (VAD) are at risk for epistaxis due to the need for anticoagulation. Additionally, these patients develop acquired von Willebrand syndrome (AvWS) due to these devices. Management is complicated by the risk of thrombosis if anticoagulation is reversed. This study sought to characterize the clinical features and management of epistaxis in this high-risk population. Methods Retrospective review of adults with VAD and epistaxis necessitating inpatient consultation with the otolaryngology service were included. Results 49 patients met inclusion criteria. All patients had a presumed diagnosis of AvWS. An elevated INR (> 2.0) was present in 18 patients (36.7%). Anticoagulation was held in 14 (28.6%) patients, though active correction was not necessary. Multiple encounters were required in 16 (32.7%) patients. Spontaneous epistaxis was associated with multiple encounters (p = 0.02). The use of hemostatic material was associated with a lower likelihood of bleeding recurrence (p = 0.05), whereas cauterization with silver nitrate alone was associated with a higher likelihood of re-intervention (p = 0.05). Surgery or embolization was not required urgently for any patient. Endoscopy under general anesthesia was performed for one patient electively. Mean follow up time was 16.6 months (σ = 6.3). At six months, 18 (36.7%) patients were deceased. Conclusion While these patients are at risk for recurrent spontaneous epistaxis, nonsurgical treatment without active correction of INR or AvWS was largely successful. Placement of hemostatic material, as opposed to cautery with silver nitrate, should be considered as a first-line treatment in this group. Multidisciplinary collaboration is critical for successful management.